2021
DOI: 10.3390/ijms22189886
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Antioxidant Activity and Ligand Basicity in the Dipicolinate Series of Oxovanadium(IV) and Dioxovanadium(V) Complexes

Abstract: Oxidative stress plays an important role in the pathogenesis of many serious diseases, including cancer, atherosclerosis, coronary artery disease, Parkinson’s disease, Alzheimer’s disease, stroke and myocardial infarction. In the body’s natural biochemical processes, harmful free radicals are formed, which can be removed with the help of appropriate enzymes, a balanced diet or the supply of synthetic antioxidant substances such as flavonoids, vitamins or anthocyanins to the body. Due to the growing demand for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…In order to confirm the structure of the synthesized crystal of complex compound, we described the IR spectrum of the dipicolinate oxovanadium(IV) complex (Figure 3) [41]. The characterization results presented in Tables 1 and 2 and their validation with theoretical calculations and literature data indicate that the vanadium complex synthesis was correct [41,42]. The synthesized complex was used for 2-propen-1-ol oligomerization.…”
Section: Resultsmentioning
confidence: 87%
“…In order to confirm the structure of the synthesized crystal of complex compound, we described the IR spectrum of the dipicolinate oxovanadium(IV) complex (Figure 3) [41]. The characterization results presented in Tables 1 and 2 and their validation with theoretical calculations and literature data indicate that the vanadium complex synthesis was correct [41,42]. The synthesized complex was used for 2-propen-1-ol oligomerization.…”
Section: Resultsmentioning
confidence: 87%
“…The compound [VOO(dipic)](2-phepyH) • H 2 O was obtained as crystals, while compound [VO(dipic)(dmbipy)] • 2 H 2 O was obtained as a powder. All crystal parameters of the complex have been published in the literature [34]. In [VOO(dipic)](2-phepyH) • H 2 O crystal structure, the lengths and angles of bonds characterizing the geometry of the dioxo-(pyridine-2,6-dicarboxylate)-vanadium(V) cation have values similar to other crystal structures containing this oxovanadium cation(V) [34].…”
Section: Resultsmentioning
confidence: 70%
“…All crystal parameters of the complex have been published in the literature [34]. In [VOO(dipic)](2-phepyH) • H 2 O crystal structure, the lengths and angles of bonds characterizing the geometry of the dioxo-(pyridine-2,6-dicarboxylate)-vanadium(V) cation have values similar to other crystal structures containing this oxovanadium cation(V) [34]. XRD studies of the crystals of the synthesized compound, [VOO(dipic)](2-phepyH) • H 2 O, confirmed that this complex compound crystallizes in the monoclinic P21/c space group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polycarboxylate oxovanadium(IV) and dioxovanadium(V) complex compounds (Figure 1) were synthesized according to the procedures described in the literature: [22,23] for [24] for [VO(ida)(bipy)]•2 H 2 O (Com-pound 3), [25] [VO(dipic)(dmbipy)]•2 H 2 O (Compound 4). The complex compound [VOO(dipic)](2-phepyH)•H 2 O was synthesized in crystalline form and all data specifying the XRD analysis of this complex have been described in the publication [22].…”
Section: Synthesismentioning
confidence: 99%